2019
DOI: 10.1155/2019/7430860
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Resource Deployment Approach to Mobile Microlearning: From Energy-Saving Perspective

Abstract: Mobile Microlearning, a novel fusion form of the mobile Internet, cloud computing, and microlearning, becomes more prevalent in recent years. However, its high deployment and operational costs make energy saving in cloud become a concerning issue. In this paper, to save energy consumption, a resource deployment approach to cloud service provision for Mobile Microlearning is proposed. Chinese Lexical Analysis System and Dynamic Term Frequency-Inverse Document Frequency (D-TF-IDF) are adopted to implement resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…• Nursing education (Bian et al, 2014) • Medical training and health professions (Simons, Foerster, Bruck, Motiwalla and Jonker, 2015) • Language training (Fang, 2018) • Engineering topics (Zheng et al, 2019) • Programming skills (Skalka and Drlik, 2019) Research showed that microlearning helps improve students' motivation, participation in instruction and performance. Jahnke et al (2020) provide an extensive overview of microlearning research.…”
Section: Types Of Microlearningmentioning
confidence: 99%
“…• Nursing education (Bian et al, 2014) • Medical training and health professions (Simons, Foerster, Bruck, Motiwalla and Jonker, 2015) • Language training (Fang, 2018) • Engineering topics (Zheng et al, 2019) • Programming skills (Skalka and Drlik, 2019) Research showed that microlearning helps improve students' motivation, participation in instruction and performance. Jahnke et al (2020) provide an extensive overview of microlearning research.…”
Section: Types Of Microlearningmentioning
confidence: 99%
“…Mobile devices (MDs) have become extremely popular in recent years due to their mobility and convenience [1,3]. Meanwhile, the functionality of the application for MDs becomes increasingly powerful [3], which leads to lack of local resources of MDs, such as computing resources, storage, and energy [4,5]. To this end, computing offloading for MDs has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are enthusiastic to determine the potential factors that drive learning and to maximize the positive influence of micro learning on the learning experience. The deployment of rich, colorful and multi‐mediated micro learning resources has been initialized alongside the large‐scale development of cloud‐based services, which aims to provide mobile learners affordable, efficient, continuous and stable micro learning service (Zheng et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%